Strategi UPP Dalam Meningkatkan Kehadiran Kaum Bapak Pada Ibadat - Alfa Imanuel Leobisa; Hendrik A. E. Lao; Andrian Wira Syahputra (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The participation of fathers in church services has become a concern among church leaders. This research aims to explore the strategy of the Fellowship Development Unit (UPP) in increasing the attendance of fathers at worship. This research aims to determine the strategies used by UPP to increase the attendance of fathers at worship services. This research is a library research. Data was collected through various journals and information related to the title of the article. The results of the research show that UPP's strategy in increasing the attendance of fathers at worship includes: (1) forming small groups of fathers, (2) organizing special activities for fathers, (3) increasing the involvement of fathers in church services, and (4) developing the leadership of fathers. The factors that influence the success of this strategy are the leader's commitment, congregation support, and the example of the fathers. The findings of this research can provide input for churches in designing development programs for fathers to increase their participation in worship and church life.